Preparation and characterization of MoS2 thin films for thermoelectric applications using the PVD technique - dos Passos, Joede; Oliveira, Adhimar Flavio; Rubinger, Rero Marques (Journal of Applied Materials and Technology, 2026)
Molybdenum disulfide (MoS2) is a two-dimensional material with electronic and thermal properties that make it promising for thermoelectric applications. This research presents the results of synthesizing and characterizing MoS2 thin films obtained by Physical Vapor Deposition (PVD) on silicon dioxide (SiO2) substrates. Three experimental approaches were explored to assess how changes in deposition conditions affect the material quality. In the first trial, films were formed from commercial MoS? powder in a sulfur-rich (S2) atmosphere using a PVD tubular furnace. Next, water vapor (H2O) was added to the process to observe possible improvements in material formation. Finally, silver doping was investigated, introduced during deposition to examine structural and vibrational changes in the MoS2. The samples were characterized by Optical Microscopy (OM) and Scanning Electron Microscopy (SEM), as well as Energy Dispersive Spectroscopy (EDS), used to evaluate surface morphology and composition. X-ray Diffraction (XRD) was employed to identify the crystalline structure, while Raman Spectroscopy revealed the E2g1 and A1g vibrational modes, associated with the crystallinity of the material. The results indicated that the presence of H2O during deposition favored the growth of more ordered films, with more intense peaks in XRD and Raman spectra. On the other hand, silver doping caused vibrational changes that suggest modifications in the electronic structure of MoS2.  These findings reinforce the material’s potential for use in thermoelectric devices and demonstrate that variations in synthesis conditions can significantly enhance its structural and functional properties.